Mesoporous cerium oxide modified bone augmentation material as well as preparation method and application thereof
By conducting in-situ synthesis reaction on Bio-Oss bone meal, mesoporous cerium oxide modified bone incremental materials are prepared, which solves the problem of poor binding stability of cerium oxide and Bio-Oss bone meal in the prior art, significantly improves the enzyme-like activity and antioxidant properties of the material, and provides a more favorable bone tissue regeneration environment.
Patent Information
- Application Number
- CN202510322410.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-19
- Publication Date
- 2025-04-15
AI Technical Summary
The physical mixing of existing cerium oxide and Bio-Oss bone meal leads to poor binding stability, and the enzyme-like activity and antioxidant properties of the composite material cannot be effectively improved, making it difficult to meet the clinical requirements for the efficiency and safety of bone incremental materials.
Mesoporous cerium oxide modified bone incremental material is prepared by in-situ synthesis reactions, so that mesoporous cerium oxide nanospheres are chemically combined with Bio-Oss bone meal to improve binding strength and material properties.
It significantly improves the binding force of cerium oxide and Bio-Oss bone meal, enhances the enzyme-like activity and antioxidant properties of the composite material, provides a more favorable microenvironment to promote bone tissue regeneration, and ensures the biocompatibility and long-term stability of the material.
Smart Images

Figure CN119818732A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of biomedical materials, and in particular to a mesoporous cerium oxide modified bone augmentation material, a preparation method and application thereof. Background Art
[0002] Bone augmentation materials have important clinical value in the field of dental implants and orthopedic repair, especially in repairing alveolar bone defects and promoting periodontal tissue regeneration. In the prior art, common bone augmentation materials include autologous bone, allogeneic bone and artificial synthetic materials. Among them, Bio-Oss bone powder, as a mineral material of bovine bone without organic matter, has a main component of hydroxyapatite, has a good three-dimensional network structure and a suitable pore size distribution, can effectively promote osteogenesis, and has excellent biocompatibility, and has been widely used in clinical practice. However, Bio-Oss bone powder also has some limitations in practical applications. For example, it has low biological activity, lacks bone induction ability, has limited bone tissue bonding, slow bone repair speed, and easily affects the effect of bone regeneration. Bio-Oss bone powder may cause a mild inflammatory response after implantation, thereby affecting the effect of bone integration. Therefore, it is of great clinical significance to develop a new method that can enhance the biological activity of Bio-Oss bone powder and improve its performance.
[0003] In recent years, the application of nanomaterials in bone tissue engineering has attracted widespread attention, among which cerium oxide (CeO2) has been favored due to its unique physicochemical properties and biological functions. Cerium oxide has good biocompatibility and excellent antioxidant properties, can scavenge reactive oxygen species (ROS), reduce inflammatory response, and provide a favorable microenvironment for bone tissue regeneration. Although cerium oxide has shown great application potential in bone augmentation materials, its modification and application in Bio-Oss bone powder still face many challenges. On the one hand, the existing cerium oxide is usually only physically mixed with Bio-Oss bone powder, and the combination stability of the two is poor. Cerium oxide and Bio-Oss bone powder are easily separated, resulting in the inability of cerium oxide to continue to play a role in the target site. On the other hand, the enzyme-like activity and antioxidant properties of the composite material obtained by physically mixing Bio-Oss bone powder and cerium oxide are only equal to those of pure cerium oxide, and cannot be further improved. Therefore, the effect of cerium oxide on the performance of Bio-Oss bone powder materials still needs to be further optimized to meet the clinical requirements for the efficiency and safety of bone augmentation materials.
[0004] Therefore, it is necessary to provide a new cerium oxide-modified Bio-Oss bone powder to improve the binding stability of the two and further enhance the enzyme-like activity and antioxidant properties of the composite material, so as to better promote the repair of bone defects and provide important technical support for the field of bone tissue engineering. Summary of the invention
[0005] 1. Technical issues to be resolved In view of the above technical problems, the present invention provides a mesoporous cerium oxide modified bone augmentation material, a preparation method and application thereof, which can effectively improve the binding force between cerium oxide and Bio-Oss bone powder, as well as the enzyme-like activity and antioxidant properties of the composite material, effectively remove reactive oxygen, reduce oxidative stress damage, and provide a more favorable microenvironment for bone tissue regeneration.
[0006] (II) Technical solution In order to achieve the above object, the main technical solutions adopted by the present invention include: In a first aspect, the present invention provides a mesoporous cerium oxide modified bone augmentation material, comprising a carrier and a load, wherein the carrier is Bio-Oss bone powder, and the load is mesoporous cerium oxide nanospheres; The mesoporous cerium oxide modified bone augmentation material is prepared by in-situ synthesis reaction of a cerium source, a soft template, a precipitant, a chelating agent and Bio-Oss bone powder. During the reaction, the mesoporous cerium oxide grows on the surface of the Bio-Oss bone powder and is chemically combined with the Bio-Oss bone powder.
[0007] In the mesoporous cerium oxide modified bone augmentation material as described above, preferably, the diameter of the mesoporous cerium oxide nanospheres is 90-120 nm.
[0008] In a second aspect, the present invention provides a method for preparing the above-mentioned mesoporous cerium oxide modified bone augmentation material, comprising the following steps: S1: in a solvent, a cerium source, a soft template, a precipitant, a chelating agent and Bio-Oss bone powder are subjected to an in-situ synthesis reaction to obtain a mesoporous cerium hydroxide-modified Bio-Oss bone powder composite material; S2: calcining the mesoporous cerium hydroxide modified Bio-Oss bone powder composite material to obtain a mesoporous cerium oxide modified bone augmentation material.
[0009] In the method for preparing the mesoporous cerium oxide modified bone augmentation material as described above, preferably, in step S1, the cerium source, the soft template, the precipitant, the chelating agent, the Bio-Oss bone powder and the solvent are evenly mixed to obtain a mixed solution, the mixed solution is heated to 80-90° C., and the in-situ synthesis reaction is performed for 8-10 hours to obtain a mesoporous cerium hydroxide modified Bio-Oss bone powder composite material.
[0010] In the method for preparing the mesoporous cerium oxide modified bone augmentation material as described above, preferably, in step S1, the cerium source is cerium nitrate hexahydrate, the soft template is hexadecyltrimethylammonium bromide, the precipitant is hexamethylenetetramine, the chelating agent is citric acid, the solvent is deionized water, and the diameter of the Bio-Oss bone powder is 0.25-1 mm.
[0011] In the method for preparing the mesoporous cerium oxide modified bone augmentation material as described above, preferably, in step S1, the mass ratio of the cerium source, the soft template, the precipitant and the chelating agent is (170-190):(140-160):(50-70):(40-45), and the mass ratio of the cerium source to the Bio-Oss bone powder is 2.4-7.2.
[0012] In the method for preparing the mesoporous cerium oxide modified bone augmentation material as described above, preferably, in step S1, after the in-situ synthesis reaction is completed, cooling and solid-liquid separation are performed, and then the obtained solid particles are washed and dried to obtain the mesoporous cerium hydroxide modified Bio-Oss bone powder composite material.
[0013] In the method for preparing the mesoporous cerium oxide modified bone augmentation material as described above, preferably, in step S2, under an inert atmosphere, the mesoporous cerium hydroxide modified Bio-Oss bone powder composite material is heated to 450-550°C at a heating rate of 2-4°C / min, calcined for 3-5h, and then under an air atmosphere, the temperature is increased to 450-550°C at a heating rate of 2-4°C / min, and calcined for 3-5h to obtain the mesoporous cerium oxide modified bone augmentation material.
[0014] In the method for preparing the mesoporous cerium oxide modified bone augmentation material as described above, preferably, in step S1, the mass volume ratio of the sum of the cerium source, the soft template, the precipitant and the chelating agent to deionized water is 1 g: (400-450) mL.
[0015] In a third aspect, the present invention further provides a use of the above-mentioned mesoporous cerium oxide modified bone augmentation material or the mesoporous cerium oxide modified bone augmentation material prepared by the above-mentioned preparation method in dental implantation or bone defect repair.
[0016] (III) Beneficial effects First, the mesoporous cerium oxide modified bone augmentation material of the present invention is prepared by in-situ synthesis reaction of a cerium source, a soft template, a precipitant, a chelating agent and Bio-Oss bone powder. This in-situ synthesis preparation method enables the mesoporous cerium oxide nanospheres of the load to grow on the surface of the carrier Bio-Oss bone powder through chemical bonding. Compared with physical mixing, the chemical bonding of the present invention greatly improves the bonding strength between the carrier and the load, and can avoid the risk of detachment of the load due to mechanical external force or body fluid flushing after implantation, thereby ensuring the biocompatibility and long-term stability of the material after implantation.
[0017] Second, compared with the composite material obtained by physically mixing Bio-Oss bone powder with cerium oxide or the pure mesoporous cerium oxide material, the Ce in the mesoporous cerium oxide modified bone augmentation material of the present invention is 3+The content is significantly increased, and further, the enzyme-like activity and antioxidant properties of the material are also significantly improved, which can effectively remove reactive oxygen, reduce oxidative stress damage, and provide a more favorable microenvironment for bone tissue regeneration.
[0018] Third, the high specific surface area and porous structure of the mesoporous cerium oxide nanospheres can not only enhance the biological activity of bone augmentation materials, but also provide a high-capacity loading space, providing an ideal platform for the loading and sustained release of drugs or growth factors, further promoting the proliferation and differentiation of bone cells and optimizing the bone regeneration effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a transmission electron micrograph of the mesoporous cerium oxide modified bone augmentation material prepared in Example 1; Figure 2 This is a transmission electron micrograph of the mesoporous cerium oxide modified bone augmentation material prepared in Example 2; Figure 3 This is a transmission electron micrograph of the mesoporous cerium oxide modified bone augmentation material prepared in Example 3; Figure 4 This is a scanning electron microscope image of the mesoporous cerium oxide modified bone augmentation material prepared in Example 1; Figure 5 This is the selected area electron diffraction pattern of the mesoporous cerium oxide modified bone augmentation material prepared in Example 2; Figure 6 This is a transmission electron microscope image of the mesoporous cerium oxide nanospheres prepared in Comparative Example 1; Figure 7 This is a transmission electron microscope image of the mesoporous cerium oxide nanospheres prepared in Comparative Example 2; Figure 8 XRD curves of the mesoporous cerium oxide modified bone augmentation material prepared in Example 1, mCeO2 prepared in Comparative Example 1, and Bio-Oss bone powder; Fig. 9 This is the N2 adsorption-desorption isotherm diagram of the mesoporous cerium oxide nanospheres prepared in Comparative Example 1; Fig.10 This is the pore size distribution diagram of the mesoporous cerium oxide nanospheres prepared in Comparative Example 1; Fig.11 This is an XPS graph of the mesoporous cerium oxide modified bone augmentation material prepared in Example 1; Fig.12 This is an XPS curve of the mesoporous cerium oxide nanospheres prepared in Comparative Example 1; Fig.13Zeta potential diagrams of the mesoporous cerium oxide modified bone augmentation material prepared in Example 1, the mesoporous cerium oxide nanospheres prepared in Comparative Example 1, and the Bio-Oss bone powder; Fig.14 The graph is a graph showing the absorbance variation over time at 652 nm of the oxide generated after the mesoporous cerium oxide modified bone augmentation material prepared in Example 1, the mesoporous cerium oxide nanospheres prepared in Comparative Example 1, and the Bio-Oss bone powder are immersed in TMB; Fig.15 This is a graph showing the change in the amount of O2 produced over time by the mesoporous cerium oxide modified bone augmentation material prepared in Example 1, the mesoporous cerium oxide nanospheres prepared in Comparative Example 1, and the Bio-Oss bone powder under the action of H2O2; Fig.16 This is a graph showing the effects of the mesoporous cerium oxide modified bone augmentation material prepared in Example 1 and Bio-Oss bone powder on the activity of rat bone marrow mesenchymal stem cells. DETAILED DESCRIPTION
[0020] In order to better explain the present invention and facilitate understanding, the present invention is described in detail below in conjunction with the accompanying drawings and specific implementation methods.
[0021] The present invention provides a mesoporous cerium oxide modified bone augmentation material, comprising a carrier and a load, wherein the carrier is Bio-Oss bone powder and the load is mesoporous cerium oxide nanospheres.
[0022] The mesoporous cerium oxide modified bone augmentation material of the present invention is prepared by in-situ synthesis reaction of a cerium source, a soft template, a precipitant, a chelating agent and Bio-Oss bone powder. During the reaction, the mesoporous cerium oxide grows on the surface of the Bio-Oss bone powder and is chemically combined with the Bio-Oss bone powder.
[0023] The present invention synthesizes mesoporous cerium oxide nanosphere materials in situ on Bio-Oss bone powder by a soft template method, so that the materials have uniform pore size distribution and high chemical reactivity. The mesoporous cerium oxide modified bone augmentation material of the present invention not only retains the osteoconductivity and biocompatibility of the bone augmentation material, but also significantly improves the enzyme-like activity, antioxidant activity and biological activity of cerium oxide, and can effectively remove reactive oxygen and effectively reduce oxidative stress damage after implantation. The mesoporous cerium oxide modified bone augmentation material of the present invention has a simple preparation process and excellent material properties. It is suitable for dental implantation, bone defect repair and other fields, and has broad clinical application prospects.
[0024] The in-situ synthesis preparation method of the present invention enables the mesoporous cerium oxide nanospheres of the load to grow on the surface of the carrier Bio-Oss bone powder through chemical bonding. Compared with physical mixing, this chemical bonding greatly improves the bonding strength between the carrier and the load, and can avoid the risk of detachment of the load due to mechanical external force or body fluid flushing after implantation, thereby ensuring the biocompatibility and long-term stability of the material after implantation.
[0025] Compared with the composite material obtained by physically mixing Bio-Oss bone powder with cerium oxide or the pure mesoporous cerium oxide material, the Ce in the mesoporous cerium oxide modified bone augmentation material of the present invention is 3+ The content is significantly increased, and further, the enzyme-like activity and antioxidant properties of the material are also significantly improved, which can effectively remove reactive oxygen, reduce oxidative stress damage, and provide a more favorable microenvironment for bone tissue regeneration.
[0026] In addition, the high specific surface area and porous structure of mesoporous cerium oxide nanospheres can not only enhance the biological activity of bone augmentation materials, but also provide a high-capacity loading space, providing an ideal platform for the loading and sustained release of drugs or growth factors, further promoting the proliferation and differentiation of bone cells and optimizing the bone regeneration effect.
[0027] Preferably, the diameter of the mesoporous cerium oxide nanospheres of the present invention is 90-120 nm.
[0028] The present invention also provides a method for preparing a mesoporous cerium oxide modified bone augmentation material, comprising the following steps: S1: In a solvent, a cerium source, a soft template, a precipitant, a chelating agent and Bio-Oss bone powder are subjected to an in-situ synthesis reaction to obtain a mesoporous cerium hydroxide modified Bio-Oss bone powder composite material.
[0029] S2: calcining the mesoporous cerium hydroxide modified Bio-Oss bone powder composite material to obtain a mesoporous cerium oxide modified bone augmentation material.
[0030] The present invention achieves efficient combination of mesoporous cerium oxide and Bio-Oss bone powder through a simple process, which can make up for the shortcomings of a single material, thereby significantly improving the biological activity of the material to meet the urgent needs of dental implants and bone defect repair.
[0031] The present invention uses Bio-Oss bone powder as a substrate, and directly grows mesoporous cerium oxide nanospheres on its surface through chemical bonding and interface interaction, achieving in-situ modification rather than physical mixing. Specifically, the functions of each reaction raw material are as follows: The surface of Bio-Oss bone powder provides a reaction interface for the anchoring of the cerium source. The cerium source and the chelating agent form a stable complex, which slows down the hydrolysis rate of cerium ions, avoids homogeneous nucleation in the solution, and ensures that cerium is preferentially adsorbed on the surface of Bio-Oss bone powder. The soft template self-assembles into micelles at the bone powder-solution interface, guiding the complex formed by the cerium source and the chelating agent to directional condense along the template confined space to form mesoporous cerium hydroxide nanospheres, whose mesoporous structure is retained after the soft template is removed. Then, under the action of the precipitant, the pH of the solution increases, and Ce 4+ The cerium hydroxide was gradually hydrolyzed to complete the lattice growth and chemical bonding on the surface of Bio-Oss bone powder, thereby obtaining a mesoporous cerium hydroxide modified Bio-Oss bone powder composite material.
[0032] Specifically, in step S1, a cerium source, a soft template, a precipitant, a chelating agent, Bio-Oss bone powder and a solvent are uniformly mixed to obtain a mixed solution, the mixed solution is heated to 80-90°C, and the in-situ synthesis reaction is carried out for 8-10 hours. After the in-situ synthesis reaction is completed, cooling and solid-liquid separation are carried out, and then the obtained solid particles are washed and dried to obtain a mesoporous cerium hydroxide modified Bio-Oss bone powder composite material. The drying temperature is 60-80°C, the drying time is 10-14 hours, and the diameter of the Bio-Oss bone powder is 0.25-1mm.
[0033] Preferably, the cerium source is cerium nitrate hexahydrate, the soft template is hexadecyltrimethylammonium bromide, the precipitant is hexamethylenetetramine, the chelating agent is citric acid, and the solvent is deionized water. The mass ratio of the cerium source, the soft template, the precipitant and the chelating agent is (170-190):(140-160):(50-70):(40-45), the mass ratio of the cerium source to the Bio-Oss bone powder is 2.4-7.2, more preferably 3.6, and the mass volume ratio w:v of the sum of the cerium source, the soft template, the precipitant and the chelating agent to deionized water is 1g:(400-450)mL.
[0034] Preferably, in step S2, under an inert atmosphere, such as a nitrogen atmosphere, the mesoporous cerium hydroxide modified Bio-Oss bone powder composite material is heated to 450-550°C at a heating rate of 2-4°C / min, calcined for 3-5h, and then under an air atmosphere, the temperature is increased to 450-550°C at a heating rate of 2-4°C / min, and calcined for 3-5h to obtain a mesoporous cerium oxide modified bone augmentation material.
[0035] In an inert atmosphere, the residual soft template and chelating agent are incompletely carbonized at high temperature to form a carbon skeleton network, which interacts with the hydroxyl groups of the mesoporous cerium hydroxide to temporarily support the mesoporous structure and prevent the pores from collapsing. Calcination in an air atmosphere can further remove the residual carbon to obtain a mesoporous cerium oxide modified bone augmentation material.
[0036] The present invention discovered through experimental research that mesoporous cerium oxide nanospheres are positively charged and Bio-Oss bone powder is negatively charged. The charge attraction between the mesoporous cerium oxide nanospheres with positive surface charge and the negatively charged Bio-Oss bone powder is utilized to facilitate the in-situ synthesis of mesoporous cerium oxide nanospheres on Bio-Oss bone powder.
[0037] In order to further clarify the scheme of the present invention and its technical advancement, the following is a description in conjunction with specific embodiments and technical effects.
[0038] Example 1
[0039] This embodiment provides a method for preparing a mesoporous cerium oxide modified bone augmentation material, comprising the following steps: S1: Add citric acid, hexadecyltrimethylammonium bromide, cerium nitrate hexahydrate, hexamethylenetetramine, and Bio-Oss bone powder with an average diameter of 0.65 mm into a flask, then add water, stir evenly, heat to 80°C in an oil bath, react for 10 hours, cool after the reaction, and then centrifuge. Then, wash the solid nanoparticles with deionized water and ethanol in turn, and dry in an oven at 70°C for 14 hours to obtain a mesoporous cerium hydroxide modified Bio-Oss bone powder composite material.
[0040] In step S1, the mass ratio of cerium nitrate hexahydrate, hexadecyltrimethylammonium bromide, hexamethylenetetramine and citric acid is 180:150:60:43, the mass ratio of cerium nitrate hexahydrate to Bio-Oss bone powder is 3.6, and the mass volume ratio w:v of the sum of cerium nitrate hexahydrate, hexadecyltrimethylammonium bromide, hexamethylenetetramine and citric acid and deionized water is 1g:450mL.
[0041] S2: The obtained mesoporous cerium hydroxide modified Bio-Oss bone powder composite material is placed in a tubular furnace, calcined to 500°C at a heating rate of 2°C / min under N2, and kept at 500°C for 4 hours. Then, the temperature is further increased to 500°C in air at a heating rate of 2°C / min and kept at this temperature for 4 hours to obtain a mesoporous cerium oxide modified bone augmentation material.
[0042] Example 2
[0043] This embodiment provides a method for preparing a mesoporous cerium oxide modified bone augmentation material, comprising the following steps: S1: Add citric acid, hexadecyltrimethylammonium bromide, cerium nitrate hexahydrate, hexamethylenetetramine, and Bio-Oss bone powder with an average diameter of 0.25 mm into a flask, then add water, stir evenly, heat to 85°C in an oil bath, react for 8 hours, cool after the reaction, and then centrifuge. Then, wash the solid nanoparticles with deionized water and ethanol in turn, and dry in an oven at 60°C for 12 hours to obtain a mesoporous cerium hydroxide modified Bio-Oss bone powder composite material.
[0044] In step S1, the mass ratio of cerium nitrate hexahydrate, hexadecyltrimethylammonium bromide, hexamethylenetetramine and citric acid is 170:140:50:40, the mass ratio of the cerium source to the Bio-Oss bone powder is 7.2, and the mass volume ratio w:v of the sum of cerium nitrate hexahydrate, hexadecyltrimethylammonium bromide, hexamethylenetetramine and citric acid and deionized water is 1 g:436 mL.
[0045] S2: The obtained mesoporous cerium hydroxide modified Bio-Oss bone powder composite material is placed in a tubular furnace, calcined to 450°C at a heating rate of 3°C / min under N2, and kept at 450°C for 5 hours. Then, the temperature is further increased to 450°C in air at a heating rate of 3°C / min and kept at this temperature for 5 hours to obtain a mesoporous cerium oxide modified bone augmentation material.
[0046] Example 3
[0047] This embodiment provides a method for preparing a mesoporous cerium oxide modified bone augmentation material, comprising the following steps: S1: Add citric acid, hexadecyltrimethylammonium bromide, cerium nitrate hexahydrate, hexamethylenetetramine, and Bio-Oss bone powder with an average diameter of 1 mm into a flask, then add water, stir evenly, heat to 90°C in an oil bath, react for 9 hours, cool after the reaction, and then centrifuge. Then, wash the solid nanoparticles with deionized water and ethanol in turn, and dry in an oven at 80°C for 10 hours to obtain a mesoporous cerium hydroxide modified Bio-Oss bone powder composite material.
[0048] In step S1, the mass ratio of cerium nitrate hexahydrate, hexadecyltrimethylammonium bromide, hexamethylenetetramine and citric acid is 190:160:70:45, the mass ratio of cerium nitrate hexahydrate to Bio-Oss bone powder is 2.4, and the mass volume ratio w:v of the sum of cerium nitrate hexahydrate, hexadecyltrimethylammonium bromide, hexamethylenetetramine and citric acid and deionized water is 1g:400mL.
[0049] S2: The obtained mesoporous cerium hydroxide modified Bio-Oss bone powder composite material was placed in a tubular furnace, calcined to 550°C at a heating rate of 4°C / min under N2, and kept at 550°C for 3 hours. Then, the temperature was further increased to 550°C in air at a heating rate of 4°C / min and kept at this temperature for 3 hours to obtain a mesoporous cerium oxide modified bone augmentation material.
[0050] Comparative Example 1 This comparative example provides a method for preparing mesoporous cerium oxide, which is different from Example 1 in that Bio-Oss bone powder is not added in step S1, and mesoporous cerium oxide is prepared in step S2.
[0051] Comparative Example 2 This comparative example provides a method for preparing mesoporous cerium oxide, which is different from Example 2 in that Bio-Oss bone powder is not added in step S1, and mesoporous cerium oxide is prepared in step S2.
[0052] Figure 1-Figure 3 The transmission electron microscope (TEM) images of the mesoporous cerium oxide modified bone augmentation materials prepared in Examples 1-3 are shown, wherein the darker spherical parts are mesoporous cerium oxide nanospheres, and the rest are Bio-Oss bone powder. Figure 1-Figure 3 It can be seen that the mesoporous cerium oxide nanospheres on the surface of the mesoporous cerium oxide modified bone augmentation materials prepared in Examples 1-3 all have a uniform mesoporous sphere morphology and a very rough surface. The diameter of the mesoporous cerium oxide nanospheres is about 90-120 nm.
[0053] The mesoporous cerium oxide modified bone augmentation material prepared in Example 1-2 was dispersed in deionized water and subjected to ultrasonic treatment for 1 h. After the ultrasonic treatment, the material was dropped onto a silicon wafer and a copper mesh to prepare test samples. Figure 4 Scanning electron microscope (SEM) images of the mesoporous ceria-modified bone augmentation material are shown, and Figure 5 Shown is the selected area electron diffraction (SAED) image of the mesoporous cerium oxide modified bone augmentation material.
[0054] pass Figure 4 It can be clearly seen that the mesoporous cerium oxide of Example 1 is still firmly attached to the Bio-Oss bone powder, indicating that the combination of the two is very stable. Figure 5 The diffraction patterns in the direction of hydroxyapatite (211) and cerium oxide (111) (220) are shown, which indicates that even after ultrasonic treatment, the mesoporous cerium oxide nanospheres are still attached to the Bio-Oss bone powder, showing a close connection between them. In addition, after testing, the combination of mesoporous cerium oxide nanospheres and Bio-Oss bone powder in the mesoporous cerium oxide modified bone augmentation material prepared in Example 3 is as stable as that in Example 1 and Example 2.
[0055] Figure 6 as well as Figure 7 The transmission electron microscope (TEM) images of mesoporous cerium oxide nanospheres (mCeO2) prepared in Comparative Example 1 and Comparative Example 2 are shown respectively. Figure 6 as well as Figure 7 It can be seen that the mesoporous cerium oxide nanospheres prepared in Comparative Examples 1 and 2 have uniform mesoporous sphere morphology and a very rough surface. The diameter of the mesoporous cerium oxide nanospheres is about 200-260 nm, which is larger than the diameter of the mesoporous cerium oxide nanospheres in Examples 1-3.
[0056] Performance characterization of mesoporous cerium oxide modified bone augmentation material (Bio-Oss-mCeO2), mesoporous cerium oxide nanosphere material (mCeO2) and Bio-Oss bone powder: The mesoporous cerium oxide modified bone augmentation material (Bio-Oss-mCeO2) prepared in Example 1, the mesoporous cerium oxide nanosphere material (mCeO2) prepared in Comparative Example 2, and the Bio-Oss bone powder used were characterized by physical and chemical properties, including X-ray diffraction analysis (XRD), N2 adsorption-desorption isotherm analysis, pore size distribution analysis, X-ray photoelectron spectroscopy analysis (XPS) and Zeta potential analysis.
[0057] Figure 8 The XRD curves of Bio-Oss-mCeO2 prepared in Example 1, mCeO2 prepared in Comparative Example 1, and Bio-Oss bone powder are shown in Figure 2. Figure 8 It can be seen that the position and intensity of the diffraction peak in the XRD curve of Bio-Oss-mCeO2 are consistent with the standard card of cubic fluorite structure CeO2 (PDF#34-0394) and the standard card of hexagonal hydroxyapatite (PDF#09-0432), and no other miscellaneous peaks are observed in the image, indicating that the mesoporous cerium oxide modified bone augmentation material was successfully prepared in Example 1. In addition, after testing, Examples 2-3 also successfully prepared mesoporous cerium oxide modified bone augmentation materials.
[0058] Fig. 9 as well as Fig.10 They are respectively the N2 adsorption-desorption isotherm and pore size distribution diagram of mCeO2 prepared in Comparative Example 1. Fig. 9 as well as Fig.10 It can be seen that mCeO2 exhibits a type IV isotherm with a H3 hysteresis loop, which is a characteristic of mesoporous materials, and its specific surface area is 49.147 m 2 / g, pore volume is 3.475cm 3 / g, pore diameter is 3.831nm.
[0059] Fig.11as well as Fig.12 The XPS curves of Bio-Oss-mCeO2 prepared in Example 1 and mCeO2 prepared in Comparative Example 1 are shown respectively. Fig.11 as well as Fig.12 It can be seen that the Ce in mCeO2 of Comparative Example 1 3+ The content of Ce ions is 20.85%, and the Ce content in Bio-Oss-mCeO2 of Example 1 is 20.85%. 3+ ions content is 22.75%, indicating that the mesoporous cerium oxide nanospheres have a high Ce 3+ ion content, while the Ce content of the in situ synthesized Bio-Oss-mCeO2 composite material 3+ The ion content is significantly improved, and the chemical reaction activity is better. In addition, the Ce in Bio-Oss-mCeO2 prepared in Example 2-3 is detected. 3+ The contents of Ce ions were 23.62% and 22.95% respectively. 3+ The ion content is 19.78%.
[0060] Fig.13 The Zeta potential diagrams of Bio-Oss-mCeO2 prepared in Example 1, mCeO2 prepared in Comparative Example 1, and Bio-Oss bone powder are shown in Figure 1. Fig.13 It can be seen that the Zeta potential of Bio-Oss bone powder is -6.51mV, the Zeta potential of mCeO2 is 45.3mV, and the Zeta potential of Bio-Oss-mCeO2 is -11.1mV. The single mCeO2 is positively charged, the single Bio-Oss bone powder is negatively charged, and the in-situ synthesized Bio-Oss-mCeO2 is negatively charged, indicating that the mesoporous cerium oxide nanospheres are successfully loaded on the Bio-Oss bone powder. In addition, after testing, the Bio-Oss-mCeO2 prepared in Example 2-3 is also negatively charged, and the Zeta potential is -10.7mV and -10.5mV respectively.
[0061] Test 1: TMB (3,3',5,5'-tetramethylbenzidine) is an organic compound commonly used as a chromogenic substrate for peroxidase. TMB can be oxidized by H2O2 under the catalysis of peroxidase to generate a blue product with a maximum absorption peak at 652nm. By detecting the change in absorbance, the enzyme activity can be quantitatively determined.
[0062] Based on the above principle, the changes in the peroxidase-like activities of Bio-Oss-mCeO2 prepared in Example 1, mCeO2 prepared in Comparative Example 1, and Bio-Oss bone powder were detected. Specifically, at 25°C, a HAc-NaAc buffer solution with a pH of 4 was prepared. The Bio-Oss-mCeO2 prepared in Example 1, the mCeO2 prepared in Comparative Example 1, and Bio-Oss bone powder were first dispersed in a HAc-NaAc buffer solution with a pH of 4, respectively, and the concentration of cerium oxide in the solution was kept at 50 μg / mL. Then, TMB and H2O2 were added to ensure that the concentration of TMB in the solution was 1.04 mM and the concentration of H2O2 was 40 mM. The absorbance changes of the samples at 652 nm over time were collected by an ultraviolet spectrometer, and graphs were drawn to obtain Fig.14 .pass Fig.14 It can be seen that the peroxidase-like activity of Bio-Oss-mCeO2 in Example 1 is significantly higher than that of mCeO2. In addition, the same test was performed on Examples 2-3 and Comparative Example 2, and the peroxidase-like activity of Bio-Oss-mCeO2 in Examples 2-3 was also significantly higher than that of mCeO2. According to the same mass ratio of cerium source to Bio-Oss bone powder as in Example 1, the mCeO2 in Comparative Examples 1-2 was physically mixed with Bio-Oss bone powder respectively to obtain a mixture, and the peroxidase-like activity of the mixture was detected to be basically the same as that of mCeO2.
[0063] The above test results indicate that in situ growth of mesoporous cerium oxide on Bio-Oss bone powder can enhance the peroxidase activity of the composite material, scavenge reactive oxygen species - H2O2, and has the potential to reduce the level of oxidative stress.
[0064] Test 2: The catalase-like activity of the Bio-Oss-mCeO2 prepared in Example 1, the mCeO2 prepared in Comparative Example 1, and the Bio-Oss bone powder was detected. Specifically, the Bio-Oss-mCeO2 prepared in Example 1, the mCeO2 prepared in Comparative Example 1, and the Bio-Oss bone powder were added to a PBS buffer solution at pH = 7.4, so that the final concentrations of cerium oxide and H2O2 in the system were 100 μg / mL and 3% (w / v), respectively, and the oxygen concentration was measured using a dissolved oxygen meter to obtain Fig.15In addition, the same test was performed on Examples 2-3 and Comparative Example 2, and the catalase-like activity of Bio-Oss-mCeO2 of Examples 2-3 was also significantly higher than that of mCeO2. According to the same mass ratio of cerium source to Bio-Oss bone powder as in Example 1, mCeO2 of Comparative Examples 1-2 was physically mixed with Bio-Oss bone powder to obtain a mixture, and the catalase-like activity of the mixture was basically the same as that of mCeO2.
[0065] From the above content, it can be seen that the oxygen production capacity of Bio-Oss-mCeO2 in Example 1 is significantly higher than the peroxidase-like activity of mCeO2, which indicates that the in situ growth of mesoporous cerium oxide on Bio-Oss bone powder can improve the catalase-like activity of the composite material, scavenge reactive oxygen -H2O2, and has the potential to reduce the level of oxidative stress.
[0066] Test three: The effect of Bio-Oss-mCeO2 prepared in Example 1 on the activity of rat bone marrow mesenchymal stem cells (BMSCs) was evaluated by live-dead cell staining. Specifically, the fourth generation of well-grown rat bone marrow mesenchymal stem cells were taken and 5×10 4 / well density was inoculated in a 24-well cell culture plate and cultured until the cells adhered to the wall. Bio-Oss bone powder and Bio-Oss-mCeO2 powder were prepared into suspensions with concentrations of 50, 100, and 200 μg / ml, respectively, and added to a 24-well plate. After culturing for 24 hours, the plate was washed three times with PBS, incubated with calcein and propidium iodide reagent for 30 minutes at room temperature, and then washed three times with PBS. The fluorescently labeled cells on the surface of the material were observed under a fluorescence microscope and photographed. Image J software was used to count the live and dead cells, and the cell activity quantification results were shown in Figure 2. Fig.16 As shown. Fig.16 It can be seen that the BMSCs cell activity in the Bio-Oss-mCeO2 group was good, and no obvious material toxicity was observed. Similarly, the effect of the Bio-Oss-mCeO2 prepared in Examples 2-3 on the activity of rat bone marrow mesenchymal stem cells (BMSCs) was tested in the same manner, and the cell viability was detected to be no significantly different from that of the Bio-Oss-mCeO2 in Example 1.
[0067] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A mesoporous cerium oxide modified bone augmentation material, characterized in that: It includes a carrier and a load, wherein the carrier is Bio-Oss bone powder, and the load is mesoporous cerium oxide nanospheres; The mesoporous cerium oxide modified bone augmentation material is prepared by in-situ synthesis reaction of a cerium source, a soft template, a precipitant, a chelating agent and Bio-Oss bone powder. During the reaction, the mesoporous cerium oxide grows on the surface of the Bio-Oss bone powder and is chemically combined with the Bio-Oss bone powder.
2. The mesoporous cerium oxide modified bone augmentation material according to claim 1, characterized in that: The diameter of the mesoporous cerium oxide nanospheres is 90-120 nm.
3. A method for preparing the mesoporous cerium oxide modified bone augmentation material according to any one of claims 1 to 2, characterized in that: The steps include: S1: in a solvent, a cerium source, a soft template, a precipitant, a chelating agent and Bio-Oss bone powder are subjected to an in-situ synthesis reaction to obtain a mesoporous cerium hydroxide-modified Bio-Oss bone powder composite material; S2: calcining the mesoporous cerium hydroxide modified Bio-Oss bone powder composite material to obtain a mesoporous cerium oxide modified bone augmentation material.
4. The method for preparing the mesoporous cerium oxide modified bone augmentation material according to claim 3, characterized in that: In step S1, the cerium source, soft template, precipitant, chelating agent, Bio-Oss bone powder and solvent are mixed evenly to obtain a mixed solution, the mixed solution is heated to 80-90° C., and the in-situ synthesis reaction is carried out for 8-10 hours to obtain a mesoporous cerium hydroxide modified Bio-Oss bone powder composite material.
5. The method for preparing the mesoporous cerium oxide modified bone augmentation material according to claim 4, characterized in that: In step S1, the cerium source is cerium nitrate hexahydrate, the soft template is hexadecyltrimethylammonium bromide, the precipitant is hexamethylenetetramine, the chelating agent is citric acid, the solvent is deionized water, and the diameter of the Bio-Oss bone powder is 0.25-1 mm.
6. The method for preparing the mesoporous cerium oxide modified bone augmentation material according to claim 3, characterized in that: In step S1, the mass ratio of the cerium source, the soft template, the precipitant and the chelating agent is (170-190):(140-160):(50-70):(40-45), and the mass ratio of the cerium source to the Bio-Oss bone powder is 2.4-7.
2.
7. The method for preparing the mesoporous cerium oxide modified bone augmentation material according to claim 3, characterized in that: In step S1, after the in-situ synthesis reaction is completed, cooling and solid-liquid separation are performed, and then the obtained solid particles are washed and dried to obtain the mesoporous cerium hydroxide modified Bio-Oss bone powder composite material.
8. The method for preparing the mesoporous cerium oxide modified bone augmentation material according to claim 3, characterized in that: In step S2, under an inert atmosphere, the mesoporous cerium hydroxide modified Bio-Oss bone powder composite material is heated to 450-550°C at a heating rate of 2-4°C / min and calcined for 3-5 hours, and then under an air atmosphere, the temperature is increased to 450-550°C at a heating rate of 2-4°C / min and calcined for 3-5 hours to obtain a mesoporous cerium oxide modified bone augmentation material.
9. The method for preparing the mesoporous cerium oxide modified bone augmentation material according to claim 3, characterized in that: In step S1, the mass volume ratio of the sum of the cerium source, the soft template, the precipitant and the chelating agent to deionized water is 1 g: (400-450) mL.
10. Use of the mesoporous cerium oxide modified bone augmentation material according to any one of claims 1 to 2 or the mesoporous cerium oxide modified bone augmentation material prepared by the preparation method according to any one of claims 3 to 9 in dental implantation or bone defect repair.
Citation Information
Patent Citations
Method for preparing cerium dioxide material with high specific surface area
CN102923753A
Bone implant material based on nano-enzyme drug modification and preparation method and application thereof
CN113318272A
Mesoporous cerium oxide nano material as well as preparation method and application thereof
CN117416985A
Hydroxyapatite coating loaded with cerium oxide nano-enzyme with high Ce < 3 + > content as well as preparation method and application of hydroxyapatite coating
CN119499450A
Process for preparing mesoporous ceria
CN1837053A